PENGEMBANGAN BAHAN AJAR DIGITAL INSTALASI PENERANGAN LISTRIK BERBASIS CHALLENGE BASED LEARNING (CBL) UNTUK KEMANDIRIAN BELAJAR SISWA KELAS XI TEKNIK INSTALASI TENAGA LISTRIK - Perangin Angin, Bayu Andica; Mulyana, Dadang (Universitas Negeri Medan, 2023)
Abstract The objectives to be achieved in this research are to find out: (1) Development of digital teaching materials using the Challenge Based Learning learning model as a learning medium. (2) The feasibility and effectiveness of student learning using digital teaching materials. The Challenge Based Learning Model. Research was carried out at the Imelda Private Vocational School, Medan. This research uses research and development methods or better known as Research and Development (R&D). This product development model is a series of procedures to produce learning media for Challenge Based Learning-based learning media applications on understanding Electrical Installation Concepts for secondary vocational students XI Electrical Power Installation. This product development model uses the ADDIE Lee and Owens model. The results of the research show that: The digital teaching materials with the flipbook maker-based Challenge Based Learning learning model that the researchers developed are suitable for use in the learning process. The results obtained from the assessment are: (1) Assessment of digital teaching material and media using the Challenge Based Learning learning model based on the flipbook maker that researchers developed for the